2019
DOI: 10.4102/aveh.v78i1.490
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing non-attendance to scheduled eye surgery in rural Swaziland

Abstract: To investigate factors influencing disengagement with surgical services, specifically nonattendance to scheduled eye surgery in the low-income setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…A hospital-based study within the same setting also found fear (55.9%) to be the leading reason for refusing free cataract surgery [ 94 ]. Fear was also reported among 41 subjects as one of the 3 leading reasons for not taking up eye surgery in rural Eswatini [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…A hospital-based study within the same setting also found fear (55.9%) to be the leading reason for refusing free cataract surgery [ 94 ]. Fear was also reported among 41 subjects as one of the 3 leading reasons for not taking up eye surgery in rural Eswatini [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study had cataract (48.6%) accounting for most of the ophthalmic procedures, followed by YAG laser capsulotomy (19.8%) for posterior capsular opacification and Pterygium excision Cataract extraction was the commonest reason for ocular surgery in most studies and it should be readily accessible as it has been found to be an extremely cost effective intervention capable of increasing the quality of life and productivity of the individual in 75-90% [8,9,10] of cases.…”
Section: Fig 3 Comparison Of Mean Ages Of Patients Across the Threementioning
confidence: 95%